A dictionary of chemistry - Law, Jonathan; Rennie, Richard (Oxford quick reference., 2020)
A Dictionary of Chemistry, covering all aspects of chemistry and related topics, such as physical chemistry and biochemistry, including recent developments in the field. It is supplemented by graphs, diagrams, and detailed appendices as well as useful web links which are accessible via the companion website.